SYSTEM SALES FORECAST VALUME PD BROTHER - Fatiman Fatiman; Irwan Bastian, Ir., MM Irwan Bastian, Ir., MM (Jurnal Sistem Informasi, 1999)
Starting from the ignorance of indications from a series of previous data, the authorswill try to uncover any such indication in order to obtain information that can be usedin determining pengantisipasi steps against him. is nothing but an indication of adegree of "change" that might be predicted based on the pattern of fluctuationscontained in these data.In order to minimize the discussion of "change" this, the case of the problems in PDBrother is very suitable to serve as a reference in the discussion of this topic. BrotherPD is a corporate enterprise engaged in screen printing and commercial printingequipment silk screening purposes have problems in determining the ordering ofgoods to be provided must comply with the request, so that no excess sterjadiexcessive reservations so that the negative difference between income on thereservation can suppressed as much as possible.In order to obtain the minimum level of orders that can be used to anticipate thedemand will occur, estimates is needed to explore the possibilities of "change" and itssales volume of goods traded PD Brother least one period ahead.